A Hybrid Particle Swarm Optimisation approach for Reactive Power Optimisation in electricity market. (29th March 2011) - Rajkumar, P.; Devaraj, D.
Reactive Power Optimisation (RPO) is an important issue in deregulated electricity market. This paper presents a Hybrid Particle Swarm Optimisation (HPSO) approach for solving the RPO problem in electricity market. Particle Swarm Optimisation (PSO) is a population-based search algorithm for global optimisation and has a minimum number of control parameters. In the proposed HPSO, to avoid the possibility of trapping in local optimum, genetic operators namely crossover and mutation are applied to the PSO algorithm. The proposed algorithm has been applied to find the optimal reactive power control variables in IEEE 30-bus system and promising results have been obtained.